Consumer credit and overindebtedness: the Brazilian experience = Crédito ao consumidor e superendividamento: a experiência brasileira - Miragem, Bruno (2020)
Submitted by tgoncalv@stj.jus.br (tgoncalv@stj.jus.br) on 2020-08-06T19:00:28Z No. of bitstreams: 2 consumer_credit_overindebtedness_miragem.pdf: 666194 bytes, checksum: 64f18a4c17edc8afce1f82dad4bae637 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)